Pre-twinned magnesium for improved ballistic performance. (October 2021) - Magagnosc, D.J.; Jannotti, P.A.; Ligda, J.P.; Lloyd, J.T.
Abstract: Despite promise as a lightweight structural and armor material, widespread adoption of Mg alloys remains limited. For instance, the highly anisotropic properties, arising both from the fundamental deformation mechanisms and strong texture developed during processing of wrought Mg products, result in poor performance under ballistic loading. In an effort to improve the impact performance, a novel pre-compression process was developed to introduce twins into a rolled AZ31B plate. Through sequential compression along plate transverse direction (TD) and rolling direction (RD) the resistance to penetration by a 0.30-cal fragment simulating projectile, as characterized by its V50, was increased by 13% offering equivalent protection of a plate 16% heavier than the pre-twinned plate. In addition, the dominant failure mechanism was found to change from discing to ductile hole growth. Through examination of the pre-compressed microstructures and microhardness measurements the origins of the improved performance were identified as the introduction of stable twins. Highlights: Sequential pre-compression of rolled AZ31B plates introduces stable twins. Pre-twinned AZ31B exhibits enhanced hardness and penetration resistance. Improved ballistic performance stems from suppressing a discing failure mode.